Hubungan Dukungan Sosial Dan Pengetahuan Keluarga Dengan Kekambuhan Pada Pasien Skizofrenia - Rosmina Situngkir; Kristia Novia; Nikodemus Sili Beda (Jurnal Keperawatan Florence Nightingale, 2026)
Schizophrenia is a severe chronic mental disorder with a considerably high relapse rate. Relapse is not only influenced by the patient's biological factors but also significantly determined by the external environment's support and the family's ability to manage home care. Aim: This study aimed to determine the relationship between social support and family knowledge with the relapse rate in schizophrenia patients at RSKD Dadi, South Sulawesi Province. This research was a quantitative study using a cross-sectional design. Data were analyzed using the Chi-Square statistical test to examine the relationship between variables with a significance level of α=0.05. The study results showed a significant relationship between family knowledge and the relapse rate of schizophrenia patients (????=0.01). This data indicates that families with good knowledge had patients with a low relapse rate (111 people, 85.4%), while families with poor knowledge tended to have patients with a high relapse rate. Furthermore, a significant relationship was also found between social support and the patient's relapse rate (p=0.00). Adequate family knowledge and positive social support are key factors in suppressing the relapse rate of schizophrenia patients. Educated families are able to provide better medication supervision and create a conducive home environment for the patient's recovery. It is recommended that the hospital enhance its psychoeducation programs for families to minimize the rehospitalization rate.